PENINGKATAN KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 21 DUMAI DENGAN MODEL PROBLEM BASED LEARNING MELALUI STRATEGI PEMODELAN - Romaisa Romaisa (sarasvati, 2023)
This learning practice aims to improve the ability to write descriptive texts for seventh grade students of SMP Negeri 21 Dumai with a Problem Based Learning model through modeling strategies. The subjects of this learning practice are the seventh grade students of SMP Negeri 21 Dumai, totaling 20 students. The results of this learning practice indicate that the application of modeling strategies can improve the ability to write descriptive texts in class VII students of SMP Negeri 21 Dumai both in terms of process and product. Process improvement can be seen in student activities in the learning process. This is indicated by the increase in students' attention to learning, enthusiasm, activity, and a more conducive learning atmosphere in the classroom. Improving process quality has a positive impact on improving product quality. This can be seen in the results of the students' descriptive text writing tests which have increased. It can be concluded that the modeling strategy is one of the writing strategies that can improve the ability to write descriptive text.